2007
DOI: 10.1521/suli.2007.37.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Models of Helper Behavior to Actual Practice in Telephone Crisis Intervention: A Silent Monitoring Study of Calls to the U.S. 1–800‐SUICIDE Network

Abstract: Models of telephone crisis intervention in suicide prevention and best practices were developed from a literature review and surveys of crisis centers. We monitored 2,611 calls to 14 centers using reliable behavioral ratings to compare actual interventions with the models. Active listening and collaborative problem-solving models describe help provided. Centers vary greatly in the nature of interventions and their quality according to predetermined criteria. Helpers do not systematically assess suicide risk. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 6 publications
(8 reference statements)
2
90
3
3
Order By: Relevance
“…Child helplines are general helplines, and in our study, the counselors are professional volunteers with some, but not extensive, training in handling suicidal callers, chatters, and texters. Risk assessment skills are often lacking among professional mental health providers, primary care physicians (Kalafat et al., ), and even in helplines dedicated to suicidal clients (Mishara et al., ). Mishara et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Child helplines are general helplines, and in our study, the counselors are professional volunteers with some, but not extensive, training in handling suicidal callers, chatters, and texters. Risk assessment skills are often lacking among professional mental health providers, primary care physicians (Kalafat et al., ), and even in helplines dedicated to suicidal clients (Mishara et al., ). Mishara et al.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has consistently shown that helplines are effective tools in reducing distress and suicidality for help‐seekers. Most of these studies concern telephone‐based services (Gould, Kalafat, HarrisMunfakh, & Kleinman, ; King, Nurcombe, Bickman, Hides, & Reid, ; Lester, ; Mishara & Daigle, ; Mishara et al., ) and one concerns chat‐based interventions (Mokkenstorm et al., ). To our knowledge, there are no published studies on the efficacy of text‐based suicide helpline services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-Four Hours Crisis Line Earlier in the twentieth century, telephone counseling was utilized to help people with suicidal ideation by religious organizations or volunteers (Mishara et al 2007). Hotlines are one of the oldest suicide prevention strategies in America (Shneidman and Farberow 1957) and the United Kingdom (Day 1974).…”
Section: Selective Strategymentioning
confidence: 99%
“…Во-первых, использование горячих линий [Mishara, Chagnon, Daigle, 2007]. Однако результаты применения этой стратегии ока-зались противоречивыми.…”
Section: теоретические аспекты проблемыunclassified